INTER-ORGANIZATIONAL COOPERATION NETWORKS IN THE TOURIST TRADE OF LENÇÓIS MARANHENSES – BARREIRINHAS (MA) - Bastos, Gisele Mendonça Furtado; Universidade Federal do Ceará/Programa de Pós-graduação em Administração e Controladoria (2022)
This research aimed to analyze the elements that make up a network of intra-organizational cooperation in the tourist trade of Lençóis Maranhenses - Barreirinhas (MA). 16 company directors and 4 representatives of public agencies were interviewed, in which the interview script was divided into: organizational; strategic; Social; and politics. Discourse analysis was used, with the help of ATLAS.ti. The results reveal that the cooperative relationships are informal and the cooperation actions established are more focused on the operational than on the strategic level. The presence of competitive-cooperative practices among companies is noted. The relationships between the actors of the tourist trade are presented in a more rational than affective way. It is concluded that the actors involved who work in the tourist activity of Barreirinhas need to identify ways of working to resolve existing conflicts and their possible solutions. This research provided insights and relevant information about inter-organizational relationships in the investigated tourist trade.